2019
DOI: 10.1111/jpn.13130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the β‐carotene oxygenase 2 genotype on the content of carotenoids, retinol and α‐tocopherol in the liver, fat and milk of rabbit does, reproduction parameters and kitten growth

Abstract: Mutations in the β‐carotene oxygenase 2 (BCO2) gene can impair the function of the enzyme that breaks down carotenoids. As a result, gradual accumulation of unoxidized carotenoids in animal tissues gives them a yellow colour. The aim of the study was to determine the content of carotenoids, retinol and α‐tocopherol in the liver, fat and milk of rabbit does with three different genotypes determined by AAT‐deletion mutation at codon 248 of the BCO2 gene and to find out whether differences in the concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…An in-frame deletion of three nucleotides in the coding sequence of this gene gene was reported to be the causative mutation of the Yellow fat recessive allele [134]. Homozygous rabbits for this mutation have an increased accumulation of xanthophylls and beta-carotene in the liver, muscle, adipose tissue, and milk without any negative effects on growth and maternal performances compared to heterozygous or homozygous rabbits for the wild type allele [135][136][137].…”
Section: Molecular Characterization Of a Biochemical Defect: The Yellow Fat Locusmentioning
confidence: 99%
“…An in-frame deletion of three nucleotides in the coding sequence of this gene gene was reported to be the causative mutation of the Yellow fat recessive allele [134]. Homozygous rabbits for this mutation have an increased accumulation of xanthophylls and beta-carotene in the liver, muscle, adipose tissue, and milk without any negative effects on growth and maternal performances compared to heterozygous or homozygous rabbits for the wild type allele [135][136][137].…”
Section: Molecular Characterization Of a Biochemical Defect: The Yellow Fat Locusmentioning
confidence: 99%
“…Moreover, dietary carotenoids increased the yellow pigmentation in rabbit meat, adipose tissue, liver, and milk. There is a high positive correlation between dietary carotenoids and their concentration in plasma, which is involved in enhancing the antioxidative properties [104,105]. Moreover, under experimental conditions, rabbits are often given large amounts of green food, covering the vitamin A requirements and enhancing their health status.…”
Section: Vitamin Amentioning
confidence: 99%
“…Furthermore, IS interacts with mitochondrial redox principles and causes renal dysfunction [9]. In addition, the inner membrane of mitochondria has a BCO2 enzyme (EC 1.14.99), and it helps in catalytic conversion of carotenoids [10]. Experimental evidence revealed that the deficiency of BCO2 contributes to the progression of renal dysfunction via the alteration of mitochondrial membrane potential [11].…”
Section: Introductionmentioning
confidence: 99%